PERLINDUNGAN HUKUM TERHADAP HAK PEKERJA ATAS PEMUTUSAN HUBUNGAN KERJA AKIBAT KEPAILITAN PERUSAHAAN MENURUT UNDANG-UNDANG KEPAILITAN DAN CIPTA KERJA - Rafael Simare Mare; Hulman Panjaitan; Paltiada Saragi (Fakultas Hukum Universitas Kristen Indonesia, 2026)
Protection of workers' rights is a fundamental aspect of labor law, which aims to ensure the fulfillment of citizens' constitutional rights to decent work and livelihood. In industrial relations practice, termination of employment due to company bankruptcy is a complex legal issue because it involves various legal interests between workers, employers, curators, and other creditors. Company bankruptcy not only results in the termination of employment but also raises issues regarding workers' rights in the form of wages, severance pay, long service awards, and other outstanding normative rights. This study aims to analyze the legal regulations regarding the protection of workers' rights who experience termination of employment due to company bankruptcy based on Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations and Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation to Become Law. This study uses a normative legal research method with a regulatory and contextual approach. The data used is secondary data consisting of primary, secondary, and tertiary legal materials. The results of the study indicate that the Indonesian legal system normatively provides protection for workers as economically disadvantaged parties in industrial relations. This protection is realized through the recognition of workers' rights as preferred creditors and through Constitutional Court Decision No. 67/PUU-XI/2013, which affirms that workers' wages must be paid first over all other types of bills. However, the implementation of this legal protection still faces various obstacles, including limited bankruptcy assets, conflicting norms between labor law and bankruptcy law, and the weak position of workers in the bankruptcy estate settlement process. Therefore, regulatory harmonization and strengthening of legal protection mechanisms are needed to ensure legal certainty, justice, and benefits for workers, which impacts corporate bankruptcy.